Digital Immediate Complete Denture for a Patient with Rhabdomyosarcoma: A Clinical Report. Issue 3 (15th January 2021) - Mendonça, Gustavo; Edwards, Sean P.; Mayers, Colin A.; Meneghetti, Priscila Ceolin; Liu, Fei
Abstract: Fabricating an immediate complete denture can be very challenging in some clinical situations. This clinical report describes a digital workflow to fabricate a printed maxillary immediate complete denture for a patient with a severely compromised maxilla. Digital data obtained by using an intraoral scanner was utilized to reconstruct the three‐dimensional (3D) image of the jaws at the desirable vertical dimension of occlusion. After performing the virtual teeth extraction and alveoloplasty, the denture base and teeth were designed. The resulting data were exported to a 3D printer for denture fabrication and the 3D printed (additively manufactured) denture was successfully inserted immediately after the surgery. After initial healing and confirmation of good retention and function, a new printed denture was fabricated by digitally duplicating the relined denture maintaining the same teeth positions but adjusting the base to a new intraoral scan of the healed ridge.